2022
DOI: 10.1101/2022.12.23.521666
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Long live the host! Proteomic analysis reveals possible strategies for parasitic manipulation of its social host

Abstract: Parasites with complex lifecycles are known to manipulate the phenotype of their intermediate hosts to increase the probability of transmission to their definitive hosts. Anomotaenia brevis, a cestode that uses Temnothorax nylanderi ants as intermediate hosts, extends the lifespan of these hosts several fold and changes their behaviour, morphology, and colouration. The mechanisms behind these changes are unknown, as is whether the increased longevity is achieved through manipulation of the parasite. Here we sh… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…Cestodes are known to release vesicles into their environment that contain miRNAs (Ancarola et al, 2020, 2017). In our study system, tetraspanin, a protein considered indicative of extracellular vesicles, was identified among the cestode proteins released into ant haemolymph, suggesting that A. brevis uses this pathway to interact with its host (Hartke et al 2022). A function of extracellular vesicles in parasite-host communication or manipulation has been suggested also in other systems (Coakley, et al, 2015; 2016; Siles-Lucas et al, 2015; Tritten & Geary, 2018), this all points to a need of our parasites living alone to communicate more with (or manipulate) their hosts.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Cestodes are known to release vesicles into their environment that contain miRNAs (Ancarola et al, 2020, 2017). In our study system, tetraspanin, a protein considered indicative of extracellular vesicles, was identified among the cestode proteins released into ant haemolymph, suggesting that A. brevis uses this pathway to interact with its host (Hartke et al 2022). A function of extracellular vesicles in parasite-host communication or manipulation has been suggested also in other systems (Coakley, et al, 2015; 2016; Siles-Lucas et al, 2015; Tritten & Geary, 2018), this all points to a need of our parasites living alone to communicate more with (or manipulate) their hosts.…”
Section: Discussionmentioning
confidence: 82%
“…4c) of these upregulated genes in parasites from highly infected hosts revealed transport functions, among which are carbohydrate transmembrane transport, regulation of pH and sodium ion transport . When comparing these genes to those proteins released into the haemolymph of host ants (Hartke et al 2022) using BLAST, we found three matching genes, none of which were annotated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The GO enrichment analysis (Figure 4c) of these upregulated genes in parasites from highly infected hosts revealed transport functions, among which are carbohydrate transmembrane transport, regulation of pH and sodium ion transport. When comparing these genes to those proteins released into the haemolymph of host ants (Hartke et al, 2022) using blast, we found three matching genes, none of which were annotated.…”
Section: Influence Of Parasite Load On Cestode Gene Expressionmentioning
confidence: 99%
“…Furthermore, similar to the ant DEGs, we performed enrichment analysis on the extracted KEGG IDs from EGGNOG mapper using clusterProfiler. Finally, to investigate whether some of those genes encode for proteins that are secreted into haemolymph of the host ants (Hartke et al, 2022), we blasted (blast v.2.9.0; Altschul et al, 1990) the cestode DEGs against the RNA sequences of secreted cestode proteins.…”
Section: Differential Gene Expression Analysismentioning
confidence: 99%